Spatial and temporal resource partitioning in a mixed‐species colony of avian echolocators. Issue 2 (16th February 2023) - Sadanandan, Keren R.; Tan, Hui Zhen; Lim, Hong Yao; Tan, Yi Gain; Lee, Grace; Chan, Lena; Pei, Yifan; Rheindt, Frank E.; Baldwin, Maude W.
Abstract: Resource partitioning may facilitate the coexistence of sympatric species with similar ecological requirements. Here, we study a colony of unusual echolocating birds called swiftlets, which nest underground on an island off the coast of Singapore. The colony comprises two congeneric swiftlet species, black‐nest swiftlets ( Aerodramus maximus ) and edible‐nest swiftlets ( A. fuciphagus ), nesting at high densities and in close proximity. Bioacoustic recordings and monitoring of nesting biology at the site across multiple seasons revealed significant differences in echolocation calls as well as survival rates between the species, with the larger black‐nest swiftlet nesting at locations with the highest fledging rates. We also observe an additional off‐season breeding peak by the smaller species, the edible‐nest swiftlet. Unexpectedly, off‐season egg‐hatching rates were significantly higher compared with the rates during the shared breeding season (mean difference = 14%). Our study on the breeding biology of these echolocating cave‐dwelling birds provides an example of spatial and temporal strategies that animals employ to partition resources within a confined habitat. Abstract : Swiftlets are unusual birds that nest in dark caves and can navigate using echolocation. We study an underground colony of 2 congeneric swiftlets and find differences in their life history strategies, echolocation calls, and offspring survival rates. We document interspecific spatial segregation of nests as well as staggered breeding seasonality between both species.